PET in neurotherapeutic discovery and development - Chassé, Melissa; Vasdev, Neil (Neurotherapeutics, 2025)
Positron emission tomography (PET) is a highly sensitive, quantitative imaging technique that can track sub-nanomolar quantities of positron-emitting radionuclides throughout the body. By incorporating such radionuclides into molecules of interest, we can directly assess their pharmacokinetic and pharmacodynamic (PK/PD) characteristics in vivo without changing their physicochemical characteristics or eliciting a pharmacological response. As such, PET imaging has long been used as a tool to aid drug discovery programs from preclinical biomarker validation all the way through to clinical trials. In this perspective we discuss the use of PET radioligands in central nervous system (CNS) drug discovery and development, with a focus on recent applications in psychiatry (e.g. 5-HT2A, 11β-HSD1), neuro-oncology (e.g. KRASG12C, ATM, ALK2), and neurodegeneration (e.g. amyloid beta plaques, MAPK p38), while exploring the intricacies associated with developing novel radiotracers for CNS targets. Examples highlight the preclinical and clinical uses of PET for studying biomarker function, drug candidate PK/PD, target occupancy/engagement, dosing regimen determination, clinical trial patient selection, and quantifying biomarker changes in response to treatments.